Performance Evaluation of Information Technology Governance using the COBIT 5 Framework at PT. Global Bangunan Jaya - Fajrillah, Fajrillah; Hasyim Syarif, Shamir; Hiya, Nirmadarningsih; Zulfa, Ira; Eliyin, Eliyin (Journal of Technology and Computer, 2025)
PT. Global Bangunan Jaya Riau is a company focused on providing essential building materials in Riau Province. This is driven by the rapid development in the region, including office infrastructure and road networks. The company was established to support the significant growth of construction in Riau, and due to its high competitiveness, it must maintain strong performance both in terms of product quality and customer service. To ensure that the quality and services provided by PT. Global Bangunan Jaya Riau align with the company's vision and mission, it is essential to evaluate the extent to which the organization’s IT goals support its overall business objectives. This evaluation is carried out using the COBIT 5 framework, focusing on the EDM (Evaluate, Direct, Monitor) domain. The research process involves three stages of analysis: assessing the current IT capability level, identifying the desired capability level, and analyzing the gap between the two. Data for this study were collected through questionnaires. The results indicate that the IT processes at PT. Global Bangunan Jaya Riau have been effectively implemented, achieved, and well-managed.